Mathematical Resilience and Academic Science Emotion in Students: New Insights from Canonical Correlation Analysis - Umi Mahmudah; Moh. Muslih (Jurnal Penelitian Pendidikan IPA, 2025)
This research aims to explore the correlation between mathematical resilience and academic science emotion and provides new insights into this association through the application of canonical correlation analysis. The study involved a sample of 191 students from a state university in Central Java, Indonesia. Participants completed self-report measures to assess their levels of mathematical resilience and academic science emotion. Data was collected by randomly distributing questionnaires to students, evaluating five indicators of academic resilience (self-efficacy, planning, control, low anxiety, persistence) and three indicators of science emotions (class-related emotions, learning-related emotions, test emotions). Canonical correlation analysis was conducted to examine the multidimensional relationship between these variables and identify underlying patterns and associations. The analysis, conducted using R programming, yielded canonical correlation coefficients of 0.785, 0.396, and 0.119, indicating a significant positive linear relationship between the analyzed variables. These findings provide insight for educators and policymakers to design interventions that enhance both mathematical resilience and emotional well-being in science education